DETERMINANTS OF GROWTH OF OFF BALANCE SHEET ACTIVITIES OF PRIVATE SECTOR BANKS: EMPIRICAL EVIDENCE FROM INDIA - Swain, Anil Kumar; Panda, Ganesh Prasad (International Journal of Research -GRANTHAALAYAH, 2017)
Off-balance sheet activities play a probatory role in helping the banks to hedge their financial assets in the on-balance sheet and enhancing the profitability of the banks. These are mainly the fee based incomes of banks having no or a little investment. Off balance sheet activities are an intriguing part of the financial statements. Presented as footnotes to accounts, these contingent items have an important economic impact that affects the future as well as the current shape of an institution. Off-balance sheet activities also help to improve the commercial banks’ scope of operations, and diversification of product lines and earnings. The business of financial intermediaries has witnessed a large increase in the use of off balance sheet activities during the last 40 years. This growth that have come as a response to the need of corporate and firms for different types of guarantees did have a conflicting impact on financial stability and bank soundness. This study is designed to investigate the OBS exposure of Indian Private Sector banks. This study found that CRAR and LT positively affect the OBS activities where as NNPA negatively affects the OBS of private sector banks and there is a relationship of 89 % of net profit with OBS activities of private sector banks.